RESPON PERTUMBUHANAN DAN HASIL TANAMAN CABAI RAWIT (Capsicum frutescens L) TERHADAP PEMBERIAN PUPUK ORGANIK CAIR (POC) URIN SAPI SEBAGAI SUMBER NUTRISI PADA SISTEM TETES SEDERHANA - Abdurrahman Abdurrahman; Gusti Rusmayadi; Ismed Fachruzi (Universitas Lambung Mangkurat, 2019)
The low national chili production often makes the supply of chili in the market limited. Utilization of cow urine as a liquid organik fertilizer is useful as an addition to the nutrient elements of chilli plants and other plants is also done to reduce excessive cow manure which can cause problems for the environment because of increasing farm business. In this study the application of liquid organik fertilizer of cow urine was applied with a simple drip system using a dropper carried out continuously during the planting period.Thisstudyaims to determinethe effect of giving a dose of liquidorganic fertilizer of cow urine as a source of nutrition in a simple drip system and to knowing the best dose of cow organic fertilizer for growthandyield ofcayenne pepper (Capsicum Frutescens L). The method used in this study uses anexperimental methodwith a single form of randomized complete design (CRD). The factors to be examined arethe concentrationof liquidorganicfertilizer from cow's urine, namely P0 = control, P1 = 35 ml of cow urine / 1 liter of water, P2 = 70 ml of cow urine / 1 liter ofwater, P3 = 105 ml of cow urine / 1liter ofwater and P4 = 140 ml of cow urine / 1 liter of water. Variety analysis shows providing liquid organic fertilizer (POC) had a significant effect on plant height, number of plant branch books, number of fruit crops, weight of fruit crops and biomass. The conclusion obtained is the provision of treatment P3 = 105 ml of cow urine / 1 liter of water can provide good and efficient results and a simple drip irrigation system can maximize nutrient absorption in fertilizers by cayenne pepper plants.